Hadith on the Recommendation to Increase Istighfar, Narrated by Imam Ahmad No. 2234 (A Study Of The Understanding of Hadith Using Jasser Auda’s Maqāṣhid Approach) - Hasan Su'aidi; Yuliyanah Yuliyanah; Luhur Kharisman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This research focuses on understanding the hadith recommending more istighfar using Jasser Auda's maqāṣhid approach, with the aim of finding out the understanding of the hadith recommending making more istighfar narrated by Imam Ahmad no. 2234 with Jasser Auda's maqᾱṣhid approach. This research aims to understand the importance of istighfar in various aspects of human life, from spiritual to economic dimensions, as well as its impact on moral values ​​and monotheism. The research method used is descriptive qualitative research, literature-based. The research results show that istighfar is not just a recommendation, but can also become an obligation in certain situations based on the maqāṣhid syarῑ'ah approach. Jasser Auda's systems approach, which focuses on